Effects of high ambient temperature, calcium level and zinc source on zinc requirement of broilers - Lai, Pui Wah (2010)
This study was divided into four experiments, and the primary objective was to determine the effects of Zn in broilers influenced by housing environmental temperatures, dietary Ca levels, Zn sources, acidifier and their respective interactions. In Experiment 1, the chicks were assigned to a 4 x 2 factorial arrangement with four corn-soybean meal basal diets (containing 44 mg Zn/kg) supplemented with 0, 40, 60 mg/kg Zn (Diets 1, 2 and 3, respectively; 0.8% Ca for these three diets) and non-Zn supplementation, 1.6% Ca (Diet 4), and two temperature conditions (low: 26, 24,22ºC vs. high: 30, 28, 26ºC). The results showed that supplemental Zn ameliorated the adverse effect of high ambient temperature on average daily feed intake (ADFI),average daily gain (ADG) and tail feather defect score of broilers. Excess Ca disrupted Zn metabolism to exert a detrimental effect on growth and normal feathering and this was elucidated in the birds kept in low temperature condition. Both Zn supplementation and high dietary Ca reduced (p<0.001) abdominal fat accumulation. Whole carcass Zn increased linearly (p<0.001) with gradient dietary Zn concentrations, and tibia Zn content (p<0.05) responded positively to dietary Zn fortification. In low temperature conditions, broilers had higher carcass Zn, Mg (p<0.05),CP (p<0.01) but lower energy retention (p<0.001). Higher (p<0.01) monounsaturated fatty acid content was found in breast meat and abdominal fat of broilers fed Diet 1 than those given Diet 2 and Diet 3. Zinc supplementation reduced (p<0.05) serum triglyceride. In Experiment 2, effects of dietary treatments used in Experiment 1 on nutrient apparent digestibility in broilers were determined. The results indicated that increasing dietary Zn and Ca reduced the apparent digestibility of these elements. On the other hand, 60 mg/kg supplemental Zn reduced Cu, Fe (p<0.001), Mn, CP (p<0.01) and energy (p<0.001) digestibilities as compared with non-Zn supplemental broilers. High Ca diet suppressed the digestibility of P (p<0.001), Zn (p<0.01), Mg, Cu, Fe (p<0.001), Mn (p<0.01) and energy (p<0.001). These adverse effects might be related to mineral interactions in the gastrointestinal tract such as the formation of insoluble complexes or due to competition between minerals. Experiment 3 further investigated the effects of two dietary Zn (0 vs. 40 mg/kg addition) and three Ca levels (0.8%, 1.2% and 1.6%) in broilers. Basal Zn concentration (38 mg/kg) was adequate for the growth requirement of broilers. Moreover, optimum ADG was achieved in broilers fed 1.2% Ca whereas 1.6% Ca impaired (p<0.001) ADG and feed conversion ratio. As 40 mg/kg Zn supplementation was provided, 1.2% and 1.6% dietary Ca levels decreased Zn digestibility. High Ca diet (1.6%) reduced the apparent digestibility of DM, Cu, Ca (p<0.001), Fe, Mg (p<0.01), Mn (p<0.05), CP and energy (p<0.001) in broilers. The fact that high dietary Ca reduced (p=0.01) carcass fat accumulation via reduced energy digestibility was confirmed in the study herein. As dietary Zn increased, marked increase in Zn content was noted in tibia (p<0.001), slight differences found in feather (p<0.09) and liver (p<0.07) but no changes (p>0.05) in breast meat and bursa. Feather (p<0.001) and tibia (p<0.05) Ca retention were also increased as dietary Ca increased. Two dietary factors, Zn sources and dietary acidification that might affect Zn utilization were studied in Experiment 4. The chicks were assigned to a 2 (ZnO vs. ZnMet) x 3 (0, citric acid, acid mixture inclusion) factorial arrangement. Overall, Zn source did not affect (p>0.05) the growth in broilers. However, citric acid addition depressed (p<0.05) the ADFI and ADG due to changes in feed palatability. When ZnO was fed, citric acid supplemental birds had higher Zn digestibility than those fed acid mixture ration. This was caused by the low citric acid composition in the acid mixture and it was not sufficient to affect Zn digestibility. Besides, the unprotected Zn in ZnO might bind with the phosphoric acid contained in the acid mixture and consequently impaired Zn digestibility. Conversely, in ZnMet supplemental birds,acid mixture inclusion improved Zn digestibility as compared with those fed citric acid. Zinc in ZnMet was protected from chelating agents in the gastrointestinal tract, and thus, the effect of citric acid on Zn digestibility was not found. Citric acid supplementation improved minerals digestibility coefficients of P (p<0.01) and Fe (p<0.05). Zinc retention in body tissues were not affected (p<0.05) by ZnO or ZnMet. In the presence of citric acid supplementation, tibia Zn deposition in ZnMet fed broilers was greater than ZnO treatment broilers, indicating that Zn in ZnMet was protected from interaction with citric acid. It was concluded that the 40 mg Zn/kg feed recommended by NRC (1994) was valid and met the growth requirements of broilers fed corn-soybean meal diet. Higher Zn requirement than NRC (1994) recommendation was necessary for broilers under environmental stress. Excessive dietary Ca suppressed growth and Zn utilization but the Zn content in most of the organs studied was preserved. No differences were found in growth, carcass yield and tissue Zn retention in broilers supplemented with ZnO or ZnMet. Zn oxide was still being used in commercial diet because of its’ low cost. Although 3% citric acid depressed growth, DM, P and Fe digestibilities were improved. This study provided some information on the effects of Zn source,acidifier and interactions occurred between the unprotected sources (ZnO or citric acid) with protected sources (ZnMet or coated acid mixture) or among unprotected sources in broilers.